M Mendeskripsikan Prosedur Pelaksanaan Tes - Rona (FAKULTAS TARBIYAH IAI SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2021)
ABSTRACT Actually, it is not the test or measurement itself that determines the fate of students, but the interpretation of the measurement results and the measurement tools. Based on the same information, different people will give different interpretations. It is these various interpretations that must be avoided because they will be dangerous for students. It is the same if the information provided is wrong because the wrong test was used or the measurement applied was wrong. From this it can be seen how important a test is in the world of education. Thus, we cannot ignore the manufacture of a test or how to measure it, how it is administered, or how to interpret it. What is the test planning procedure, What should be considered in test planning, What are the steps in the preparation of the test. The essence of conducting testing is actually an effort to explore information that can be used as a basis for decision making. In the preparation of test planning, it is necessary to pay attention to the learning outcome test so that it can clearly measure learning outcomes. Besides that, the test should also be used as a tool to find useful information to improve student learning methods and how to teach teachers themselves. In planning the test, a grid is needed so that the objective test to be written does not deviate from the material that has been taught during the learning process and also serves as a guideline for the writer in writing each item. Keywords: learning procedures, learning and test implementation outcomes